1999
DOI: 10.1046/j.1442-2042.1999.00627.x
|View full text |Cite
|
Sign up to set email alerts
|

A case of perirenal hemangioma mimicking renal cell carcinoma

Abstract: Purpose: We present a rare case of perirenal hemangioma that was detected incidentally. Methods/Results: Radiographic examinations revealed a 3.5 cm mass at the left renal hilum adjacent to the left renal parenchyma, which was difficult to differentially diagnose from renal cell carcinoma. Tumor resection was performed successfully. Conclusions: There was no recurrence observed 14 months after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…To the best of our knowledge only two such cases of renal hemangioma arising from the renal sinus or hilum have been reported in the English literature [4,5]. Okuno et al [4] reported a case of renal hilar hemangioma, which on radiographic examination revealed a 3.5 cm mass at the renal hilum adjacent to renal parenchyma difficult to differentially diagnose from renal cell carcinoma (RCC).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…To the best of our knowledge only two such cases of renal hemangioma arising from the renal sinus or hilum have been reported in the English literature [4,5]. Okuno et al [4] reported a case of renal hilar hemangioma, which on radiographic examination revealed a 3.5 cm mass at the renal hilum adjacent to renal parenchyma difficult to differentially diagnose from renal cell carcinoma (RCC).…”
Section: Discussionmentioning
confidence: 97%
“…Okuno et al [4] reported a case of renal hilar hemangioma, which on radiographic examination revealed a 3.5 cm mass at the renal hilum adjacent to renal parenchyma difficult to differentially diagnose from renal cell carcinoma (RCC). Haas et al [5] described a similar case of renal hilar tumor, however the CECT abdomen showed an enhancing soft tissue mass interposed between the right renal hilum and inferior vena cava and posteromedial to the second part of the duodenum.…”
Section: Discussionmentioning
confidence: 98%
“…hemangiomas are nonspecific and may mimic those of transitional cell carcinoma or renal cell carcinoma (25,26).…”
Section: Rindlike Soft-tissue Masses Lymphomamentioning
confidence: 98%
“…Most renal hemangiomas are solitary, small, and unilateral. Retroperitoneal and perirenal hemangiomas are extremely rare (26).…”
Section: Perirenal Hemangiomamentioning
confidence: 99%